MODIFIED ISING MODEL FOR GENERATING BINARY IMAGES - Halim, Siana (Jurnal Informatika, 2007)
In this paper the Ising model is modified by considering its parameters as a vector that depends on the neighborhoods of the image's pixels. We applied this modification for generating binary images, provided the original image is given. An example is exposed as a result of simulation using Gibbs sampler.